Goodput and throughput comparison of single‐hop and multi‐hop routing for IEEE 802.11 DCF‐based wireless networks under hidden terminal existence. Issue 9 (27th April 2015) - Aydogdu, Canan; Karasan, Ezhan
Abstract: We investigate how multi‐hop routing affects the goodput and throughput performances of IEEE 802.11 distributed coordination function‐based wireless networks compared with direct transmission (single hopping), when medium access control dynamics such as carrier sensing, collisions, retransmissions, and exponential backoff are taken into account under hidden terminal presence. We propose a semi‐Markov chain‐based goodput and throughput model for IEEE 802.11‐based wireless networks, which works accurately with both multi‐hopping and single hopping for different network topologies and over a large range of traffic loads. Results show that, under light traffic, there is little benefit of parallel transmissions and both single‐hop and multi‐hop routing achieve the same end‐to‐end goodput. Under moderate traffic, concurrent transmissions are favorable as multi‐hopping improves the goodput up to 730% with respect to single hopping for dense networks. At heavy traffic, multi‐hopping becomes unstable because of increased packet collisions and network congestion, and single‐hopping achieves higher network layer goodput compared with multi‐hop routing. As for the link layer throughput is concerned, multi‐hopping increases throughput 75 times for large networks, whereas single hopping may become advantageous for small networks. The results point out that the end‐to‐end goodput can be improved by adaptively switching between single hopping and multi‐hopping according to the traffic load and topology. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : We investigate how multi‐hop routing affects the goodput and throughput performances of IEEE 802.11 distributed coordination function‐based wireless networks compared with direct transmission (single hopping), when medium access control dynamics such as carrier sensing, collisions, retransmissions, and exponential backoff are taken into account under hidden terminal presence. We propose a semi‐Markov chain‐based goodput and throughput model for IEEE 802.11‐based wireless networks, which works accurately with both multi‐hopping and single‐hopping for different network topologies and over large range of traffic loads.